Analysis of organic polymer based PVA/CNF membranes. (2022) - Patel, Anshika; Panwar, Varij
Abstract: Nowadays, sensors made of organic polymers are used widely in the field of electronics and numerous scientific groups because of their various properties and applications (like pressure sensors, fuel cells, biosensors). Generally, organic polymers are insulators in nature but also show other properties. In this paper, polyvinyl alcohol (PVA)/ Carbon Nanofibers (CNF) were mixed in various proportions to develop their membranes. We mainly focused on the evaluation of the properties like Dielectric Constant, Conductivity, and Dissipation Factor within the 20 Hz to 10 MHz range of frequency. 1gm pure PVA with 19 ml of DI water and CNF with different proportions were blended for the development of the membrane. Through an impedance analyzer, the difference in properties of membranes for varying proportions of CNF was analyzed. We deduced from the curves that the membrane containing 0.01gm CNF displays the best results.